(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The research work assessed wildlife extension measures and its effectiveness in Old Oyo National Park. Purposive sampling was used to select the respondents from the total population. The demographic factors of the respondents revealed that male recorded the highest with 71.0% with age group 31-40 years recorded the highest (41.0%). The findings also showed that majority of the respondents are married (54.0%). The level of education indicated that respondents with tertiary education recorded the highest (61.0%). Also majority of the respondents are Muslims (52.0%) while Christianity recorded 44.0%. The various wildlife extension services in the study area showed that campaign against hunting and bush burning recorded the highest with 38.0% and 26.0% respectively, followed by campaign against deforestation with 21.0% while training on agro-forestry is the least with 2.0%. The effectiveness of the identified extension practices on wildlife conservation showed that the identified extension are slightly effective recorded the highest with 38.0%, followed by moderately effective with 33.0% while ineffective recorded the least with 4.0%. The methods been used to disseminate the extension services in the study area, in which focus group discussion recorded the highest with 39.0%, followed by radio and television with 22.0% while Newspaper/journal/magazine recorded the least with 6.0%. The challenges facing extension services delivery in the study area revealed that inadequate funding of some extension activities are the major challenges with 31.0%, followed by inadequate number of extension personnel with 21.0% while inadequate commitment personnel is the least with 5.0%.